Bosch en portada: de la pintura al món de l’edició - Alcoy, Rosa (Materia: Revista internacional d'Art, 2016)
The magnetic power of Hieronymus Bosch’s work is not unnoticed in the publishing world. Beyond the almost essential image of his creations on the book covers of specific bibliography focused on the master or his immediate environment, his paintings have been used by a large number of publishing houses. The latter use the work of the master for their publications, of different content, to take advantage of the fascination that they cause. In order to create seductive claims on the readerand to offer a relevant picture for the publication, fragments of his creations — mostly the best known — have been selected or reworkings of some specific but recognizable motifs have been made.